Catalysis Concepts in Medicinal Inorganic Chemistry. Issue 27 (25th February 2019) - Alonso‐de Castro, Silvia; Terenzi, Alessio; Gurruchaga‐Pereda, Juan; Salassa, Luca
Abstract: Catalysis has strongly emerged in the field of medicinal inorganic chemistry as a suitable tool to deliver new drug candidates and to overcome drawbacks associated to metallodrugs. In this Concept article, we discuss representative examples of how catalysis has been applied in combination with metal complexes to deliver new therapy approaches. In particular, we explain key achievements in the design of catalytic metallodrugs that damage biomolecular targets and in the development of metal catalysis schemes for the activation of exogenous organic prodrugs. Moreover, we discuss our recent discoveries on the flavin‐mediated bioorthogonal catalytic activation of metal‐based prodrugs; a new catalysis strategy in which metal complexes are unconventionally employed as substrates rather than catalysts. Abstract : Therapeutic catalysis : This Concept article highlights the main strategies employed to design catalytic metallodrugs and bioorthogonal catalytic processes for the activation of prodrugs.